STUDI DESKRIPTIF TENTANG EFEKTIFITAS PENGAWASAN PERIZINAN REKLAME DI KOTA SURABAYA - Agnesia Margaretha Gunawan (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2020)
Advertisement controlling is an effort to make sure that the establishment of the advertisement in the field in accordance with permission granted and to find any irregularities like unlicensed advertisement, the specification and location of advertisment are not suitable by licensed permitted, advertisement held on pedestrian, for doing the corrective action of those things. The facts show that the unlicensed advertisement could be find on all around street in Surabaya. These irregularities are seen by data of advertisement sweeping Satpol PP Surabaya. In 2012, there are 13.482 advertisements swept by Satpol PP Surabaya. This amount raises in 2013, there are 16.925 advertisement and 19.989 in 2014. These fact indicates there are problems of permission advertisements control in Surabaya. This study aims to describe how effective control of advertisement permission in Surabaya. Surabaya chosen as the locus in this study because of Surabaya is a big city as central economic activities in East Java that has more than twenty thousand points billboards and other advertisement along the roads and the general area in Surabaya. This research was conducted by using the method of descriptive qualitative. This research used purposive and snowball techniques informants. Data were obtained from interviews and analyzed using data reduction techniques, data presentation and conclusion throughout the data collection process. The results of this study indicate that the controlling of advertisement have not effective yet. These caused by less of human resources of Satpol PP Surabaya, minimum operational tools by quantity and quality, and less intensity of controlling.